Superior Orbital Fissure Syndrome in a Patient with Partially Treated Granulomatosis with Polyangiitis: A Case Report - Sharma, Prayush; Datta, Abhijit; Haq, Syed Atiqul (Annapurna Journal of Health Sciences, 2023)
Superior orbital fissure syndrome (SOFS) is a collection of symptoms caused by compression of structures just anterior to the orbital apex. The optic nerve is spared which differentiates superior orbital fissure syndrome from orbital apex syndrome. The causes are trauma, neoplasms, infections, inflammation and vascular phenomena. SOFS in granulomatosis with polyangitis (GPA) is a rare association and has been found only in some case reports till date. This rare case highlights development of SOFS and multiple serious adverse effects of glucocorticoid in an inappropriately treated patient with GPA without renal or pulmonary involvement.